Independência das produções em experimentos com culturas olerícolas - Benz, Vilson (2011)
Knowledge of the variability of production among the experimental plots within the protected environment, both in space and along the different crops, it is necessary, since it allows reducing the error by increasing the reliability of the results with the experimental techniques and adoption of appropriate cultural management practices . Therefore, the aim of this study was to characterize the spatial and temporal independence of fruit production between plots of vegetable crops grown in the greenhouse. We used data from the production of blank experiments conducted in greenhouse crops with zucchini, peppers, green beans and lettuce, the Department of Crop Science, Federal University of Santa Maria. With the values of individual production were simulated different sizes of plots as the number of plants in the crop row. To check the randomness of the data distribution, we applied the test sequences between plots within the row and grouped in individual crops, and crops of the same piece of individual and grouped. The randomness production between plots is favored when they are formed by a greater number of plants. The realization of a low number of samples is enough to make production of the plots over the course of random samples taken. Clusters larger than two crops and plots formed by more than two plants is the most effective combination for reducing the nonrandomness of the production of zucchini crops. The use of 10 plants per plot in experiments with chili is enough that there are lines that lack of randomness in the production of fresh fruit. In experiments conducted with bean pods in a plastic greenhouse using plots with more than four basic units makes random production of fresh fruit within the lines. As for experiments without protection or high-tunnel plots should be more than three basic units. Plots with more plants favor of independence in the production of fresh biomass in experiments with lettuce in a protected environment.